Enlightenments of spatio-temporal varied hydrological processes on water supply for agricultural irrigation in a semi-arid area - Xiaoying Qiao; Jiaxin Bian; Ziyu Wang; Qian Zhang; Ning Wang; Lei Shi; Yue You (Journal of Hydrology: Regional Studies)
Study region: Yuxi River Basin, a typical semi-arid region between the Mu Us Sandy Land and the Loess Plateau. Study focus: In arid and semi-arid regions, limited research has addressed how hydrological processes affect irrigation demand, especially under varying evaporation and recharge conditions. This research gap constrains water resources utilization and ecosystem protection. By combining the stable isotope method with water resources assessment, this study analyzed the hydrologic characteristics and proposed a coordinated surface–groundwater irrigation strategy based on spatiotemporal dynamics of evaporation and recharge. New hydrological insights: In most areas of the Yuxi River basin, groundwater is the main source of the river, accounting for 89.24 % and 88.18 % of river recharge during dry and wet periods, respectively. Except for June, river water remains a reliable source for agricultural irrigation during the irrigation season. Reservoirs and lakes significantly influence local evaporation and surface–groundwater interactions, with distinct spatio-temporal differences in the upstream and midstream sections. Furthermore, due to the combined influence of groundwater, tributaries, evaporation, and open water bodies, there is river water recharging groundwater in areas around river confluences, lakes, and res-ervoirs, with recharge percentages reaching 90.98 % and 81.63 % during dry and wet periods, respectively. Thus, groundwater should be the preferred irrigation source in these areas during May, July, and August. This isotope-based method offers scientific guidance for sustainable irrigation management in arid and semi-arid regions.